Lessons learned from a natural resource disaster: The long-term impacts of the Long Island Sound lobster die-off on individuals and communities. (February 2022) - Seara, Tarsila; Owens, Adrien; Pollnac, Richard; Pomeroy, Robert; Dyer, Christopher
Abstract: In 1999, the Long Island Sound American lobster population experienced a severe mortality event, resulting in the abrupt demise of this culturally and economically important fishery. While studies have investigated the environmental and biological causes and effects of this event, little has been done to understand its social, economic, psychological, and cultural impacts. In this study, we interviewed lobstermen and seafood wholesalers who were affected by the die-off to understand their experiences and perceptions of impacts, and factors influencing their capacity to adapt. We compared our findings to those in the sole socio-economic impact assessment conducted in the aftermath of the event. Our findings show that the die-off had profound and lasting impacts on individuals, their families, and communities with little evidence of a successful recovery. The lack of effective and comprehensive recovery or assistance plans, combined with challenges impeding fishery diversification, significantly hindered the ability of lobstermen to adapt. The lessons learned from this case study can inform future action to address impacts and maximize adaptive capacity in fishing communities experiencing environmental changes and shifts in species distributions due to climate change and other anthropogenic factors. Highlights: In 1999, the Long Island Sound American lobster population experienced a severe mortality event. We interviewed fishery stakeholders to understand their perceptions of impacts and adaptation. Our findings show that the die-off had lasting social impacts with little evidence of recovery. The lack of effective assistance and impediments to fishery diversification hindered adaptation. Results can inform action to address impacts of climate change and other anthropogenic factors.